1999
DOI: 10.1080/02724939992608
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology and clinical signs of bacterial meningitis in children admitted to Goroka Base Hospital, Papua New Guinea, 1989–1992

Abstract: Children aged 1-59 months admitted to Goroka Base Hospital with signs suggestive of meningitis were recruited to determine what proportion of such children have clinical or bacterial meningitis and to investigate the bacterial aetiology. A laboratory classification of definite, probable, possible, indeterminate and no meningitis was established. Thirty per cent of 697 children had a final clinical diagnosis of meningitis, 12% had culture-proven bacterial meningitis (case fatality rate 34%) and 10% had probable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 18 publications
3
35
1
Order By: Relevance
“…A lack of independent association between meningitis and seizures per se within the age range for febrile convulsions in hospitalized children has also been reported from children in Papua New Guinea. 15 Notably, we found that 20% of admissions with seizures outside the age range for febrile convulsions and 10% of children with partial seizures had meningitis.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…A lack of independent association between meningitis and seizures per se within the age range for febrile convulsions in hospitalized children has also been reported from children in Papua New Guinea. 15 Notably, we found that 20% of admissions with seizures outside the age range for febrile convulsions and 10% of children with partial seizures had meningitis.…”
Section: Discussionmentioning
confidence: 64%
“…When culture is negative, "possible" or "probable" cases are typically defined by CSF leukocyte count and/or CSF/blood glucose ratio. 4,12,15 However, pleocytosis may be caused by aseptic meningitis, viral meningitis, or possibly even prolonged convulsions. 16 Furthermore, proven bacterial meningitis may present with clear CSF and a low CSF leukocyte count.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies from the highlands of Papua New Guinea, where there is no malaria transmission 8 and from countries in Africa with holo-endemic Plasmodium falciparum malaria, 9,15 neck stiffness and a bulging fontanel were independently associated with ABM. Other features such as refusal to eat, staring eyes, and convulsions were inconsistent associates.…”
Section: Introductionmentioning
confidence: 92%
“…[5][6][7][8] Diagnosis and management can therefore be challenging, 9 especially when young children with ABM present with non-specific features, including lethargy or irritability rather than the classic clinical signs of meningeal irritation. 10 In malaria-endemic areas, the symptoms and signs of severe malarial illness can overlap with those of ABM, further complicating assessment.…”
Section: Introductionmentioning
confidence: 99%